IMPLEMENTATION OF TRADITIONAL RULES IN POLICY FOR SUSTAINABILITY OF LOCAL CULTURE - Herman Lawelai; Anwar Sadat; Andy Arya Maulana Wijaya (Jurnal Inovasi Penelitian, 2021)
In the face of globalization, local culture has tremendous challenges in maintaining its survival. Appropriate solutions must be devised to strengthen the durability of local culture as social capital in today's society. The Laporo Tribe's Sampua ceremony in Galanti Village is one of the traditions affected by globalization. This sort of study employs quantitative methodologies and a descriptive approach to analyze and explain changes in societal cultural and social patterns in great detail. The analysis of policy implementation indicators, such as communication, resources, disposition, and bureaucratic structure, is the subject of this study's research. This study finds, based on the data conducted, that the Sampua traditional ceremony is an obligatory ritual for families with daughters and has been performed here. Customary and religious rulers are entirely entrusted with the Sampua rite's resources, preparation, and execution in the hopes of a successful celebration. Sara can postpone the annual party until an additional agreement is reached because the family celebrates without Sara's knowledge.